The impact of (artificial intelligence techniques) on mental games and improving the performance of a series of skills using the ball tool in rhythmic gymnastics for second-year students - Hamza, Asst. L. Ghufran Bashir (Sulaimani Journal for Humanities, 2026)
Rhythmic gymnastics is a sport that demands high levels of motor skills, precise mental focus, and the ability to control balance and motor coordination. Despite this, most training programs primarily focus on physical aspects, neglecting the important role of mental games in enhancing athletic performance. This research aims to study the impact of mental games on the performance of second-year female rhythmic gymnastics students by analyzing their role in improving focus, motor control, and reducing stress during performance. The research employed an experimental methodology, dividing a sample of second-year female students into two groups: an experimental group that underwent rhythmic gymnastics training combined with the application of mental games, and a control group that received traditional training without mental games. Pre- and post-tests were conducted to compare the impact of mental games on the students' performance. The results showed that mental games had a clear positive effect on the students' performance in rhythmic gymnastics, helping to: improve performance; enhance motor coordination; reduce anxiety and stress during exercises and competitions; develop the students' overall skill performance; and increase self-confidence and motivate the students to perform at their best. Based on the findings, the research recommends: integrating mental games into rhythmic gymnastics training programs to enhance athletic performance; using mental visualization techniques to help gymnasts improve their performance; training coaches to incorporate mental games into training curricula; and conducting broader studies to explore the impact of these games on different age groups and skill levels. The research confirmed that mental games play a significant role in improving performance in rhythmic gymnastics, proving their effectiveness in enhancing focus, balance, and motor control, thus making them an essential tool for developing gymnasts' skills in this sport.
Keywords: Artificial intelligence techniques; brain games; rhythmic gymnastics; ball game